Effect of Saline Water with Varying Levels of Sar and Ca : Mg Ratios on Growth and Yield of Wheat and Soil Properties - Kumar, V; Kumar, D; Chauhan, C P.S (Annals of Arid Zone, 2016)
Effect of different Ca : Mg ratios, SAR levels and two salinity levels of irrigation water were studied on growth and yield of HD 1593 wheat ( Triticum aestivum L. ) and properties of soil. Plant height, number of spikelets and grains/spike and grain yield/barrel were markedly affected with poor quality waters. Depression in grain yield was maximum (56.9%) with EC of 10 m mhos/cm and least (40.0%) with Ca : Mg ratio of 1:8 over control. Although main effects of SAR and Ca : Mg ratios were non-significant for all the traits yet additional yield losses occurred with the higher levels of salinity. Higher values of SAR and Mg/Ca ratios also drastically affected grain yield. There was more salt build-up with saline water than with SAR values and Ca : Mg ratios. Na content increased dramatically in all the treatments, whereas Ca and Mg were maximum at EC 10 m mhos/cm but their high contents were associated to the lower levels of SAR and Ca : Mg ratios. Mg was twice to that of Ca at SAR 10 having Ca : Mg ratio of 1 : 8 and EC 10 m mhos/cm whereas the same was 1 : 1 in other treatments. Contents of Cl and SO4 rose considerably with salinity levels, however remained unchanged with other treatments.